Aktuelle Probleme der EU - Alexander Dilger (Westfälische Wilhelms-Universität Münster, Institut für Organisationsökonomik, 2016)
Die EU hat aktuell zahlreiche Probleme. Zehn dieser Probleme werden behandelt. Insgesamt können sie die EU in ihrer Existenz bedrohen, doch diese Herausforderungen bieten auch Chancen zur Reform und Erneuerung der EU. – – The EU has currently several problems. Ten of these problems are examined. All in all they can threaten the very existence of the EU. However, these challenges also offer prospects to reform and renew the EU.
Keywords: D70; F15; F22; F50; H77; 650